(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted in the laboratories and climate rooms of the Bio-control unit college of Agriculture / Baghdad University to study of effect constant tempreture on development time of predator and accumulated degree days of predator D.manihoti . The results also showed differences between the development periods of the predator D.manihoti according to the rearing temperatures being, 31.44 and 18.13 and 13.34 and 12.5 days at temperatures 20 , 25 , 30 and 35 ± 2 ° C, respectively . the lowest developmental threshold of egg , larval stage I, II and III and the pupal stage as well as the duration from egg to adult reached 8.98, 8.78, 8.63, 12.58, 8 ° and 9 C° respectively, while 42.37, 28.24, 47.16, 43.85 and 139 heat unit, for the accumulated day degrees . The accumulated day degree of period from egg to adult was 303 heat units. Optimum temperature was 33.32 C° while Upper threshold was 42.39 Cₒ for D.manihoti respectively.